Unraveling the Role of Curriculum in Teacher Decision Making. (February 2018) - Siuty, Molly Baustien; Leko, Melinda M.; Knackstedt, Kimberly M.
Teachers make numerous decisions each day, yet processes undergirding these decisions are elusive and have not been the subject of many in-depth investigations within special education. The purpose of this qualitative investigation, therefore, was to complete a micro-level analysis of the influence of curriculum on 11 middle school teachers' decisions regarding reading instruction for middle school age struggling readers. Using the theoretical framework of teachers' literacy-related decision making proposed by Ruppar, Gaffney, and Dymond, the authors conducted interviews and observations during one school year to examine how teachers make curricular decisions based on their access to a prescribed, research-based reading intervention curriculum. Findings indicate the availability of such a curriculum facilitated teachers' decision making around individualizing instruction and increased their self-efficacy, leading to the conclusion that a bidirectional relationship exists between curriculum and (a) beliefs, (b) self-efficacy, and (c) individualization. Implications for future research and practice in middle school teacher preparation are discussed.